2023
DOI: 10.1111/liv.15646
|View full text |Cite
|
Sign up to set email alerts
|

Independent endothelial functions of PIEZO1 and TRPV4 in hepatic portal vein and predominance of PIEZO1 in mechanical and osmotic stress

Abstract: Background & AimsPIEZO1 and TRPV4 are mechanically and osmotically regulated calcium‐permeable channels. The aim of this study was to determine the relevance and relationship of these channels in the contractile tone of the hepatic portal vein, which experiences mechanical and osmotic variations as it delivers blood to the liver from the intestines, gallbladder, pancreas and spleen.MethodsWall tension was measured in freshly dissected portal veins from adult male mice, which were genetically unmodified or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 74 publications
0
3
0
Order By: Relevance
“…However, other studies have shown that piezo 1 regulates cell response to mechanical stress by controlling Ca 2+ influx, and that piezo 1 expression increases in red blood cells and hepatic portal endothelial cells when subjected to mechanical forces. Calcium ion inflow increases through calcium osmotic channels ( 42 , 46 , 47 , 48 ). Our results showed that liraglutide decreased atrial pulse pressure and piezo 1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…However, other studies have shown that piezo 1 regulates cell response to mechanical stress by controlling Ca 2+ influx, and that piezo 1 expression increases in red blood cells and hepatic portal endothelial cells when subjected to mechanical forces. Calcium ion inflow increases through calcium osmotic channels ( 42 , 46 , 47 , 48 ). Our results showed that liraglutide decreased atrial pulse pressure and piezo 1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Yoda2 is a structurally modified version of Yoda1 with the pyrazine ring replaced by 4-benzoic acid. This substitution significantly improves Piezo1 agonist activity with concentrations similar to those of Yoda1 (Endesh et al, 2023). Like Yoda1, Yoda2 also stabilizes open conformations of Piezo1, and its enhanced efficacy is likely due to the negative charge and more desirable pharmacokinetic properties of 4-benzoic acid at physiological pH relative to neutral pyrazine rings (Parsonage et al, 2022).…”
Section: Piezo1 Agonistsmentioning
confidence: 94%
“…The functional coupling between PIEZO1 and TRPV4 characterized in human umbilical vein ECs is likely dependent on the vascular bed, as activation of PIEZO1 or TRPV4 in hepatic portal vein ECs have opposing independent effects promoting relaxation and contraction, respectively. 69…”
Section: Role Of Piezos In the Vasculaturementioning
confidence: 99%